KONTRIBUSI STATUS GIZI DAN TINGKAT KESEGARAN JASMANI TERHADAP HASIL BELAJAR PENJASORKES SISWA KELAS V SD NEGERI 003 PULAU SEKOPUNG SENTAJO KABUPATEN KUANTAN SINGINGI - Indrawani Indrawani; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on observations and experience as well as the findings of the authors of the learning outcomes of physical education in SDN 003 student Sekopung Pulau Sentajo Singingi Kuantan district, many students still learning outcomes penjasorkesnya low. This is presumably due to low nutritional status and physical fitness of students of SDN 003, so the authors wanted to do research on the contribution of nutritional status and physical fitness level of the student learning outcomes. This type of research is correlational while samples were students of class V totaling 27 people with a total sampling technique. This research was conducted in SDN 003 Sekopung Pulau Sentajo and time research was conducted in September-October 2016. The data in this study were obtained from tests of nutritional status by measuring height and weight of students, test TKJI and value MID semester for learning outcomes. After normality test results followed by a normal distribution of data so that the product moment correlation was found: Contributions The nutritional status (X1) on learning outcomes penjasorkes (Y) students in 003 public primary schools Sekopung Pulau Sentajo of 17.31%. Contributions Freshness physical (X2) contribute to the learning outcomes of students in SDNpenjasorkes 003 Palau Sekopung Sentajo of 19.49%. Contributions nutritional status (X1) and physical fitness (X2) jointly contribute to the learning outcomes of students in SDN 003 Sekopung Pulau sentajo of 31.02% .8.Keywords: Nutritional Status, Physical Freshness, Learning Outcomes